Global Corporations: Corporate Environmental Accountability and the Future of Sustainability (Global Journal of Science Frontier Research, 2017)
Global corporations have contributed enormously to the deteriorating global ecology. GCs in resource extraction industries wreak the worst havocs on environment, thereby dislocating the ecosystems. GCs that operate in developing countries render the future of sustainability unpromising. The unpromising future of sustainability stems from the laissez-faire environmental behavior of GCs. Ecological crisis has galvanized movement for corporate environmental accountability and sustainability future. GCs that operate in developing countries render the future of sustainability unpromising. The unpromising future of sustainability stems from the laissez-faire environmental behavior of GCs. A global environmental architecture is needed to enforce corporate environmental accountability and sustainability.
Keywords: ecological crisis; global corporations; environmental accountability; sustainable development; environmental architecture